Pulmonary tuberculosis presenting with tubercular myocarditis and shock in an adolescent child - Dinkar Yadav; Geeta Gathwala; Anita Saxena; Kapil Bhalla (Journal of Family Medicine and Primary Care)
Involvement of the heart in children with tuberculosis (TB) generally affects the pericardium; however, the myocardium of a child being affected alone and leading to systolic heart dysfunction has rarely ever been reported. We report a case of a 12-year-old child who presented to Pediatric Emergency Services with severe hypotension (BP <5th percentile for the age) and was subsequently diagnosed with severe left ventricular (LV) dysfunction, with an ejection fraction of less than 15%. During the hospital stay, after an exhaustive workup, the child was diagnosed with pulmonary TB with tubercular myocarditis. The child was managed with anti-tubercular treatment (ATT) and was followed up regularly for monitoring of ejection fraction with echocardiography. The LV systolic function improved, with the ejection fraction increasing to 55%-60% at 3 months. The child is still on regular follow-up, has completed 6-month course of ATT, and is doing well.